Precision cancer therapy is impacted by oncogene-dependent epigenome remodeling - Feng Liu (Nature Portfolio, 2017)
Abstract The cancer genome provides the blueprint for identifying oncogenic mutations driving tumor growth and these mutant proteins and pathways are the targets for precision cancer therapies. However, many oncogenes are capable of reprogramming the landscape of active portion of the genome, commonly known as the epigenome. This creates fluidity, and thereby heterogeneity, that demands consideration of this additional layer of complexity for effective therapeutic design and application. Molecular dissection of the epigenome may identify oncogene-induced, actionable vulnerabilities, broadening the spectrum of precision oncology treatments.